The Employability Skills of the Overseas Filipino Workers - Torres, Beulah Rose R. (JPAIR Institutional Research, 2014)
A university tracks its graduates to determine if its curriculum has prepared students for the job market. The purpose of this study was to ascertain the self-perceived employability skills of sociology and economics graduates of Bukidnon State University, who are working overseas. The OFWs were traced by using the snowball sampling technique. Of the three measures of employability, they scored the highest on personal qualities followed by core skills and process skills. Rated the highest were ’self-awareness’ and ’initiative’ skills. By and large, the OFWs may be considered global citizens and lifelong learners if viewed through the lenses of an Australian model of employability. This implies that even if the academic credentials do not directly match with the job description. The graduates were hired on the basis of employability qualities and skills that were perhaps already embedded in the curriculum. The study concludes that the notion that discipline-based knowledge will guarantee a job is no longer applicable. Since knowledge will be outdated but nevertheless, the main component for obtaining a college degree, one of the recommendations is for the curriculum to connect transferable personality and skills development with the process of obtaining and generating knowledge. Further research must be pursued in terms of determining the specific values and attitudes that the employers of these OFWs prefer so that it would be possible for the university to identify the exact qualities and skills preferred by employers as a basis for curriculum development.